2018
DOI: 10.1149/2.0361803jes
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Au/Ag Nanostructures for Enhanced Electrochemical Performance

Abstract: The effect of nanostructuring on the electrochemical activity of a series of Au/Ag electrocatalysts, with and without graphene nanoplatelets (G) as carbon matrix support and β-cyclodextrin as capping agent, was systematically investigated using the ferri/ferrocyanide redox probe. A series of Au/Ag nanostructures with different morphologies were synthesized and characterized using a combination of spectroscopy, electron microscopy, and electroanalytical methods. Evaluation of the cyclic voltammograms obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…All these factors together enhance the most important properties of the electrode, leading to higher background currents and wider peak separation even in cases of reversible processes, which is very well documented in numerous papers. 65,66 Finally, it can be concluded that electrochemical characteristics, such as electrical conductivity, effective surface area and diffusion layer, were significantly improved due to the synergistic effect of MnO 2 and GNP combination.…”
Section: Cyclic Voltammetry Studymentioning
confidence: 96%
“…All these factors together enhance the most important properties of the electrode, leading to higher background currents and wider peak separation even in cases of reversible processes, which is very well documented in numerous papers. 65,66 Finally, it can be concluded that electrochemical characteristics, such as electrical conductivity, effective surface area and diffusion layer, were significantly improved due to the synergistic effect of MnO 2 and GNP combination.…”
Section: Cyclic Voltammetry Studymentioning
confidence: 96%
“…Au is a good NH 3 sensing material with excellent sensing properties at high temperatures, 23,29 and it has been explored for modifier of electrochemical sensor's interface due to its unique attributes. 30 Many scholars have studied the influence of Au on the sensing properties by many physical and chemical methods, which confirmed the sensitivity promotion effect by Au particles with different morphologies. Moos prepared a mixed-potential sensor with high NH 3 sensitivity using a double-layer electrode consists of SCR catalyst V 2 O 5 -WO 3 -TiO 2 and screen-printed Au, and it enables different parts of the electrode to display the electrical conductivity, catalytic activity and electrochemical activity.…”
mentioning
confidence: 95%
“…We have witnessed significant advances in not only the design and fabrication of nano-to-microsystems but also the synthesis of nanomaterials with desired size, surface properties, shape, and other physical properties. [17][18][19][20][21][22] These advances have significantly benefited the implementation of advanced electrochemical sensors for enhanced performance, device miniaturization, and system integration. Therefore, the deployment of nanotechnology to develop nextgeneration electrochemical sensors has emerged as a rapidly growing field.…”
mentioning
confidence: 99%